2000
DOI: 10.1061/(asce)0733-9429(2000)126:9(691)
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Continuous Bed Load Saltating Process

Abstract: Particle saltating motions during bed load transport are dominated by the forces acting upon particles and the random process of the particles impacting on and rebounding from the channel bed. A realtime flow visualization technique is developed in this study to measure particle saltating trajectories, corresponding velocities, and impacting and rebounding angles. Based on the experimental data, regression equations for the dimensionless saltating length, height, and velocity were obtained. A numerical model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 20 publications
3
45
0
Order By: Relevance
“…Recently, Dwivedi et al (2010Dwivedi et al ( , 2011 has shown that the higher probability of occurrence of high magnitude force on a spherical sediment particle is induced by sweep events and that outward and inward interactions are of little importance in sediment entrainment. This paper presents numerical experiments and their interpretations, which supplement and further extend previous studies of saltation (e.g., Bialik, 2011aBialik, , 2011bBombardelli et al, 2008;Lee et al, 2000Lee et al, , 2006Lukerchenko et al, 2006Lukerchenko et al, , 2008Lukerchenko et al, , 2009aLukerchenko et al, , 2009bMoreno and Bombardelli, 2012;Garcia, 1994, 1998;Wiberg and Smith, 1985, among others). New information is provided on the incipient motion of saltating grains over immobile-bed flows, associated with the existence of near-bed turbulence structures and their influence on the particles' motion.…”
Section: Introductionsupporting
confidence: 74%
“…Recently, Dwivedi et al (2010Dwivedi et al ( , 2011 has shown that the higher probability of occurrence of high magnitude force on a spherical sediment particle is induced by sweep events and that outward and inward interactions are of little importance in sediment entrainment. This paper presents numerical experiments and their interpretations, which supplement and further extend previous studies of saltation (e.g., Bialik, 2011aBialik, , 2011bBombardelli et al, 2008;Lee et al, 2000Lee et al, , 2006Lukerchenko et al, 2006Lukerchenko et al, , 2008Lukerchenko et al, , 2009aLukerchenko et al, , 2009bMoreno and Bombardelli, 2012;Garcia, 1994, 1998;Wiberg and Smith, 1985, among others). New information is provided on the incipient motion of saltating grains over immobile-bed flows, associated with the existence of near-bed turbulence structures and their influence on the particles' motion.…”
Section: Introductionsupporting
confidence: 74%
“…In addition, if it is assumed that initially the particle lies on the channel bottom and that its movement is three-dimensional, then such conditions are as follows: x p (t 0 ) = 0, y p (t 0 ) = 0, z p (t 0 ) = 0.5d, u p (t 0 ) = 2u * , v p (t 0 ) = 0 and w p (t 0 ) = 2u * . However, the initial velocities of the particle are sometimes treated as Lee et al 2000) and further several of the particles' first jumps should be discarded for the statistical analysis. This is due to the influence of the initial conditions on the height and length of saltation.…”
Section: Initiation Of Saltating Grains Movementmentioning
confidence: 99%
“…The use of these image-based techniques to study sediment transport has been steadily expanding; such techniques were first applied to studies of suspended sediment transport in turbulent flows and more recently to bedload transport. Tracking a single detected particle in a series of images is relatively easy and a number of authors have used image analysis to measure the trajectories of saltating and rolling particles (e.g., Niño et al, 1994;Hu and Hui, 1996;Lee et al, 2000;Ancey et al, 2002;Ancey et al, 2003). Tracking sediment flux is more complex and requires segmentation of all the particles in the image as a first step.…”
Section: Particle Trajectories and Velocities Using Ptvmentioning
confidence: 99%